Pulmonary endocrine cells of Aymara Indians from the Bolivian Andes. - Williams, D (1993)
INTRODUCTION: There is evidence to suggest that life at high altitude causes changes in the population of pulmonary endocrine cells, possibly because of exposure to chronic hypoxia. A study was made of the populations of pulmonary endocrine cells in three Aymara Indians and three Mestizos of La Paz (3600 m), Bolivia, which were compared with those in four white lowlanders. METHODS: Pulmonary endocrine cells were immunolabelled for neurone specific enolase and their two major secretory products, gastrin releasing peptide and calcitonin, and their numbers expressed per cm2 of tissue section. RESULTS: No differences in morphology, number, content, or distribution of immunoreactive cells were found when the native highlanders were compared with the lowlanders. CONCLUSIONS: If chronic hypoxia as such exerts an influence on human pulmonary endocrine cells it was not apparent in this morphological study. There was no increase in gastrin releasing peptide containing pulmonary endocrine cells, such as have previously been seen in patients with pulmonary hypertension characterised by plexogenic pulmonary arteriopathy. This may be due to the fact that in plexogenic pulmonary arteriopathy there is free migration of smooth muscle cells. Although three of the highlanders in this present study showed pulmonary vascular remodelling, this was in contrast only modest.